2021
DOI: 10.3390/biomedicines9030250
|View full text |Cite
|
Sign up to set email alerts
|

Mucosa-Associated Lymphoid Tissue 1 Is an Oncogene Inducing Cell Proliferation, Invasion, and Tumor Growth via the Upregulation of NF-κB Activity in Human Prostate Carcinoma Cells

Abstract: Prostate cancer is one of the most common seen malignancies and the leading cause of cancer-related death among men. Given the importance of early diagnosis and treatment, it is worth to identify a potential novel therapeutic target for prostate cancer. Mucosa-associated lymphoid tissue 1 (MALT1) is a novel gene involved in nuclear factor κB (NF-κB) signal transduction by acting as an adaptor protein and paracaspase, with an essential role in inflammation and tumorigenesis in many cancers. This study investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 50 publications
(58 reference statements)
4
17
0
Order By: Relevance
“…Unlike LNCaP cells, both PC-3 and DU145 cells have constitutively active NF-κB signaling [ 48 , 49 ]. Our recent study verified that MALT1 is an NF-κB-upregulated oncogene, and a positive feedback loop was found in prostate carcinoma cells [ 27 ]. In alignment with CAPE, an NF-κB signaling inhibitor, the current study proves that CAPE blocked NF-κB activity by downregulating MALT1 expression in PC-3 cells ( Figure 3 ).…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…Unlike LNCaP cells, both PC-3 and DU145 cells have constitutively active NF-κB signaling [ 48 , 49 ]. Our recent study verified that MALT1 is an NF-κB-upregulated oncogene, and a positive feedback loop was found in prostate carcinoma cells [ 27 ]. In alignment with CAPE, an NF-κB signaling inhibitor, the current study proves that CAPE blocked NF-κB activity by downregulating MALT1 expression in PC-3 cells ( Figure 3 ).…”
Section: Discussionsupporting
confidence: 54%
“…The 5′-DNA fragment (−1 to −6313) of MALT1 , according to the sequence from GenBank (AP005018.1), was synthesized by Invitrogen. The human MALT1 reporter vector was constructed by cloning the DNA fragment into the pGL3-Basic reporter vector (pbGL3) (Promega Biosciences, Madison, WI, USA) with Hind III sites, as described previously [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, several other studies have identified MALT1 as a central regulator of NF-κB-mediated cancer progression. Both pancreatic ductal adenocarcinoma (PDAC) and prostate cancer (PCa) cells show increased MALT1 expression that contributes to tumor malignancy and metastasis [ 89 , 90 ]. Silencing or pharmacological inhibition of MALT1 reduces the proliferative and invasive potential of the tumor cells both in vitro and in vivo.…”
Section: The Role Of the Cbm Complex In Solid Tumorsmentioning
confidence: 99%